Shared Reflections Offered by Listening to Johnny Mbizo Dyani’s Born Under the Heat - Mtshemla, Sinazo; Verghese, Ben (Kronos: Southern African Histories, 2024)
Originally written as a lecture-presentation for the 2021 South African Society for Research in Music (SASRIM) conference, this text shares our ongoing collaborative study of Born Under the Heat, an album by Johnny Mbizo Dyani. Our research tracks the record(ings) to mark potential pathways for thinking about networks of sociality and solidarity that underpin the production of such politicised cultural work, as well as how we listen to and/or may read it. We trace how the album, recorded in 1983, was born out of festival-gatherings in Lagos, Gaborone and Amsterdam as well as Dyani’s memories/remembering of home (from Duncan Village to Dorkay House, perhaps) when exiled in Scandinavia. By reiterating literal and symbolic modes of travel which Born Under the Heat took, as an object and as a concept/project, we aim to explore multiple routes and forms archival, repatriation and restitution projects continue to find in the postapartheid present.